Peranan Hukum Dalam Mencapai Keadilan dan Kesejahteraan Terhadap Kehidupan Masyarakat - Nirwana, Rena Putri; Lewoleba, Kayus K (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In its role as public administrator, the state upholds the ideals of progress, aspiration, and responsiveness to community needs through the enactment of progressive legislation. The state was established with the purpose of achieving community welfare. Law enforcement officers, particularly judges, stress eternal justice alongside legal clarity (rechtsvaardigheit) while resolving conflicts. It is critical to show that the law and its enforcers, particularly judges, have the moral fortitude to prove that the legislation is necessary to achieve societal good. The goal of this research is to understand what justice means in Indonesian law and to outline the legal framework that would allow Indonesia to build a legal system that is perfect and achieves the concept of a welfare state. Normative legal study often makes use of descriptive analysis as a research method. information derived from secondary sources, as well as primary, secondary, and tertiary legal documents.